Analysis of public food procurement in relation to dairy products and their quality criteria - Brukało, Katarzyna M.; Nowak, Justyna; Fras, Neza; Kowalski, Oskar; Gabrijelčič Blenkuš, Mojca (Frontiers in Nutrition, 2023)
Introduction Public procurement of food is key to ensuring proper nutrition with high-quality products in public institutions such as schools and kindergartens. However, it should not be considered a mandatory expenditure from public finances but rather an investment in health promotion. Materials and methods A total of 1,126 public procurement orders processed by schools and kindergartens in Poland during the period from November 2022 to March 2023 were analyzed. Ultimately, 197 public procurement orders meeting the inclusion criteria were considered for analysis. Based on these orders, 2,753 food products classified as dairy and its derivatives were extracted. The ordered quantities of individual products were analyzed, as well as their descriptions (quality characteristics). Results Criteria related to composition were most commonly described, the most common criterion was the fat content and the absence of preservatives. On the second places were organoleptic characteristics, where taste and consistency expectations were most frequently specified. Sustainable public procurement criteria were the least frequently mentioned and were treated as highly marginal. Conclusion Introducing minimum standards for the descriptions of dairy products in terms of organoleptic characteristics, composition features, and sustainability criteria will improve the quality of dairy products supplied to public institutions, particularly schools and kindergartens.